ENT Disorders Presenting with Ophthalmological Manifestations:An Overview - Sathyalakshmi M H; Girish F Hongal (Asian Journal of Medical Research, 2020)
Background: It is important to diagnose the condition early and manage aggressively. It is often difficult to cure orbital cellulitis due to late treatment and may cause blindness if left untreated because of optic nerve compression. Both orbital abscess and cavernous sinus thrombosis may lead to intracranial spread of infection, such as meningitis or cerebral abscess with high morbidity and possible mortality.Subjects and Methods:A total number of 124 cases of ophthalmological manifestation caused by various ENT diseases, mostly paranasaltumourextensions; nasopharyngeal tumour and furunculosis of nose were analyzed in a retrospective study in relation to their age, sex, clinical,radiological and histopathologicalprofile.Results: Direct nasal endoscopy(DNE), Fibre optic Flexible nasopharyngoscopy was Useful. HRCT scan was considered as the most dependable investigating tool. Different modalities of medical and surgical treatment have been adopted according to location and nature of diseases.Conclusion: Aclose co-operationand team effort required between otorhinolaryngologist and ophthalmologist to overcome this kind of challenges.